Transcription factor NF-κB, interleukin-1β, and interleukin-8 expression and its association with tobacco smoking and severity in chronic obstructive pulmonary disease - Yadav, Ravi Shanker; Kant, Surya; Tripathi, Prashant Mani; Pathak, Anumesh K; Mahdi, Abbas Ali (Gene reports, 2022)
Chronic obstructive pulmonary disease (COPD) prevalence increases with tobacco smoking, suggesting a relationship between disease severity and an increased rate of systemic symptoms with smoking. To evaluate IL-1β, IL-8 and NF-κB expression in COPD patients with smoking and non-smoking habits and determine their levels with disease severity compared to respective healthy controls. One hundred seventy-six subjects (88 COPD cases and 88 healthy controls) details demographic smoking, and disease severity enrolled in the study. Interleukin transcript and protein levels were measured by quantitative real-time PCR and enzyme-linked immunosorbent assay (ELISA). Statistical Package for the Social Sciences (SPSS) software version 21.0 was used to analyse the data. Statistical significance was set at p < 0.05. IL-1β, IL-8 and NF-κB mRNA levels were significantly higher (p < 0.001) in COPD cases than in healthy controls. NF-κB increased (1.50-folds) in patients with COPD compared to that in controls. NF-κB, IL-1β and IL-8 mRNA expression were significantly higher in smokers with COPD than non-smokers (p < 0.0001). With pack-year NF-κB, IL-1β and IL-8 transcript levels increased and showed a significant positive correlation (p < 0.0001). Moreover, with increasing pack-years, COPD severity was also significantly elevated (p < 0.0001). The Pearson correlation showed a significant positive, strong correlation with the severity of the patients. The intercorrelation between IL-1β and IL-8 and NF-κB showed a significant weak positive correlation between IL-1β and IL-8 (r = 0.30, p = 0.001); however, NF-κB showed no association (0.22, p = 0.04) either with IL-1β or IL-8. IL-1β and IL-8 expression correlated with COPD severity, which worsened with pack-years tobacco smoking. •IL-1β, IL-8 and NF-κB mRNA levels were significantly higher in COPD cases than healthy controls.•NF-κB, IL-1β, IL-8 mRNA expression was significantly higher in smokers COPD patients than non-smokers.•Pack-year showed the IL-1β, IL-8 transcript levels were increased with pack-year.•Pack-years significantly influence COPD severity.•IL-1β and IL-8 was correlated to smoking and COPD severity